Gastric Band Port Site Fixation: Which Method Is Best? - Corinne E. Owers; Sarah M. Barkley; Roger Ackroyd (Hindawi Limited, 2015)
Laparoscopic adjustable gastric banding is a popular and successful bariatric surgical technique. Although short-term complications are few in number, long-term complications are more common. One such complication is flippage of the gastric band port. This study compares three popular methods of port fixation and demonstrates that fixation with nonabsorbable mesh helps to prevent port flippage when compared to other techniques, reducing the need for repositioning operations.